An Innovative Lightweight Composite Sandwich Panel System for Prefabricated Buildings - Cui, Yanqiang (Curtin University, 2020)
The thesis develops an innovative lightweight sandwich panel system with fiber reinforced geopolymer composite skin and Polyurethane foam core for prefabricated buildings considering sustainability and energy efficiency. It is made of industrial waste and good insulation materials, hence leads to low energy consumption in construction applications. It has good mechanical properties and reasonable vibration serviceability, light weight and low cost, therefore great potentials for application in prefabricated structures.